Pelanggaran Masa Iddah - Eky Fallah Septiani; Muhammad Hasan Bisyri (Jurnal Hukum Islam, 2018)
This present study aims to explore various factors affecting some residents in Pasirkratonkramat village, West Pekalongan sub-district, Pekalongan city in violating ‘iddah’ (a waiting period that must be observed by women after both a divorce and death of their spouse). A qualitative approach presenting data of descriptive analytics was employed in this socio-legal study. The widows who were in the iddah, their husband, and parents participated in this research. This study reveals that all of the nine widows did not apply the iddah appropriately in relation to Islamic law and the compilation of Islamic laws. In reality, the widows were in a relationship, accepted a marriage proposal, or even married the man in the iddah. This fact was due to several factors, namely: low educational, economic, work environmental, and social (lifestyle) backgrounds. Additionally, the results have exposed that the violation of the iddah was caused by the low level of legal awareness performed in this village by regarding four indicators. First, the residents’ knowledge of this paradigm was still low. Second, the people’s understanding did not affirm the rules of iddah asserted in Islamic law. Third, they showed low level of attitudes toward the terms and conditions of iddah. Lastly, their law-based behavior distorted the principles of iddah. Therefore, the legal awareness of the people in this village was categorized into the low level.